Correlated Population Genetic Structure in a Three-Tiered Host-Parasite System: The Potential for Coevolution and Adaptive Divergence. (6th October 2021) - Colosimo, Giuliano; Jackson, Anna C; Benton, Amanda; Varela-Stokes, Andrea; Iverson, John; Knapp, Charles R; Welch, Mark
Abstract: Three subspecies of Northern Bahamian Rock Iguanas, Cyclura cychlura, are currently recognized: C. c. cychlura, restricted to Andros Island, and C. c. figginsi and C. c. inornata, native to the Exuma Island chain. Populations on Andros are genetically distinct from Exuma Island populations, yet genetic divergence among populations in the Exumas is inconsistent with the 2 currently recognized subspecies from those islands. The potential consequences of this discrepancy might include the recognition of a single subspecies throughout the Exumas rather than 2. That inference also ignores evidence that populations of C. cychlura are potentially adaptively divergent. We compared patterns of population relatedness in a three-tiered host-parasite system: C. cychlura iguanas, their ticks (genus Amblyomma, preferentially parasitizing these reptiles), and Rickettsia spp. endosymbionts (within tick ectoparasites). Our results indicate that while C. c. cychlura on Andros is consistently supported as a separate clade, patterns of relatedness among populations of C. c. figginsi and C. c. inornata within the Exuma Island chain are more complex. The distribution of the hosts, different tick species, and Rickettsia spp., supports the evolutionary independence of C. c. inornata . Further, these patterns are also consistent with two independent evolutionarily significant units within C. c. figginsi . Our findings suggest coevolutionary relationships between the reptile hosts, their ectoparasites, and rickettsial organisms, suggesting local adaptation. This work also speaks to the limitations of using neutral molecular markers from a single focal taxon as the sole currency for recognizing evolutionary novelty in populations of endangered species.